Effect of Microwave Radiation on the Thermal Properties of the Electroexplosive Copper Nanopowder; Progress in Electromagnetics Research Symposium (PIERS-Toyama) - Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Igumnov V. S. Vladislav Sergeevich; Chumerin P. Yu. Pavel Yurievich; Gubarev F. A. Fedor Aleksandrovich (2018, 2018)
Title screen